Vers quelle évaluation de la réflexivité en contexte de formation initiale des enseignants ? - Antoine Derobertmasure; Arnaud Dehon (Université de Provence, 2009)
In the French Belgium Community, secondary teacher education is based on 13 skills presented in a decree defining teacher education. Among these 13 skills, one of them focuses on the primary importance of developing student teachers' reflectivity during their training. Although this notion seems to be important from a theoretical and political point of view its inclusion into the training of teachers is difficult. This difficulty is related to the definition of the understanding and to the assessment of this dimension. This contribution tries to answer those questions.